The Meaning of the Message of Human Relations with Himself and Others in the Film "A Million Loves for Him" - Rahayu Putri Purnama Bismaini; Anis Endang SM; Asnawati Asnawati (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study aims to determine the meaning of the message of human relations with themselves and others in the film "Sejuta Sayang Untuknya". This research uses descriptive qualitative research methods with data collection techniques namely observation, documentation and literature study. The theoretical basis used is Roland Barthes' semiotic analysis consisting of denotation, connotation and myth. The results of the study indicate that the meaning of the message of human relations with himself is: (a) work ethic which is divided into 5, namely working lawfully, studying hard, being disciplined, being responsible, adhering to principles. (b) imitating signatures, (c) forgiving, (d) honest which is divided into 2, namely honest in words and honest in deeds. The meaning of the message of human relations with each other is: (a) manners which are divided into 3, namely with older people, talking to parents, greeting when visiting and meeting. (b) please help, (c) be rude to parents, (d) say thank you.